Virus Entry: Looking Back and Moving Forward. Issue 13 (22nd June 2018) - Helenius, Ari
Abstract: Research over a period of more than half a century has provided a reasonably accurate picture of mechanisms involved in animal virus entry into their host cells. Successive steps in entry include binding to receptors, endocytosis, passage through one or more membranes, targeting to specific sites within the cell, and uncoating of the genome. For some viruses, the molecular interactions are known in great detail. However, as more viruses are analyzed, and as the focus shifts from tissue culture to in vivo experiments, it is evident that viruses display considerable redundancy and flexibility in receptor usage, endocytic mechanism, location of penetration, and uncoating mechanism. For many viruses, the picture is still elusive because the interactions that they engage in rely on sophisticated adaptation to complex cellular functions and defense mechanisms. Graphical abstract: Unlabelled Image Highlights: Studies using a broad combination of technologies have provided detailed information on the entry and uncoating of many animal viruses. Not only the identity of cell surface receptors but their distribution in plasma membrane and in microdomains defines cell tropism and infection efficiency. The majority of viruses enter by endocytic mechanisms and penetrate into the cytosol intracellularly from a variety of different organelles. The picture is often elusive because many viruses display redundancy in receptor choice and entry strategy.